Inspector Maigret and the Teleromanzo: A Case Study of Early Italian Television - Elena Dagrada (Series. International journal of tv serial narratives)
The "teleromanzo", or "romanzo sceneggiato" (here translated as "TV novel") is a most peculiar narrative genre of early RAI. It significantly shaped early Italian television, becoming a cornerstone of RAI’s production from its mid-1950s inception. Broadcast from 1954, teleromanzi symbolized RAI’s educational mission under Italy’s state broadcasting monopoly, which lasted until 1972. Inspired by two of the three John Reith’s public service broadcasting principles, teleromanzi aimed to educate and entertain, improving cultural literacy and public consensus aligned with the ruling party. Teleromanzi are defined by three features: literary sources, theatrical staging, and installment structure. They adapted mainly 19th-century classics to entertain and teach Italian to a largely illiterate population. Early technical constraints necessitated theatrical staging, perpetrated by using stage actors known for clear diction and cultural gravitas. The installment structure fostered a loyal audience, ensuring ongoing interest and value assimilation, particularly of Catholic values. By the 1960s, RAI experimented with serial elements, also adapting works by authors like Georges Simenon into series such as "Le inchieste del Commissario Maigret"(1964- 1972), directed by Mario Landi and starring Gino Cervi. This series hybridized teleromanzo and serial formats, maintaining installment narratives while introducing recurring characters and figurative stereotypes. Its success underscored the effectiveness of teleromanzo’s blend of education and entertainment, influencing contemporary television narratives, while reflecting Italian television’s evolution and societal changes, beyond demonstrating rare chronological progression and thematic coherence. As a matter of fact, this Maigret series has much more in common with the teleromanzo and its cultural aura than with the rules of television seriality properly speaking, which were still unknown in Italy at that time. It testifies to an experimental phase of seriality, or a pre-serial seriality, whose most fertile aspect lies precisely in its capacity to integrate the formula of the teleromanzo and to enrich it with potentially serial elements, while retaining the auratic and humanist dimension imposed by the cultural educational project designed by early Rai of the monopoly.